Safely balancing a double-edged blade: identifying and mitigating emerging biosecurity risks in precision medicine - DiEuliis, Diane; Giordano, James J. (Frontiers in Medicine, 2024)
Tools and methods of precision medicine are developing rapidly, through both iterative discoveries enabled by innovations in biomedical research (e.g. -genome editing, synthetic biology, bioengineered devices). These are strengthened by advancements in information technology and the increasing body of data -as assimilated, analyzed, and made accessibleand affectable -through current and emerging cyber -and systems-technologies. Taken together, these approaches afford ever greater volume and availability of individual and collective human data. Machine learning and/or artificial intelligence approaches are broadening this dual use risk; and in the aftermath of COVID19, there is growing incentive and impetus to gather more biological data from individuals and their environments on a routine basis. By engaging these data -and the interventions that are based upon them, precision medicine offer promise of highly individualized treatments for disease and injury, optimization of structure and function, and concomitantly, the potential for (mis)using data to incur harm. This double-edged blade of benefit and risk obligates the need to safeguard human data from purloinment, through systems, guidelines and policies of a novel discipline, cyberbiosecurity, which, as coupled to ethical precepts, aims to protect human privacy, agency, and safety in ways that remain apace with scientific and technological advances in biomedicine. Herein, current capabilities and trajectories precision medicine are described as relevant to their dual use potential, and approaches to biodata security (viz.-cyberbiosecurity) are proposed and discussed.